Anesthetic Management for Urgent Caesarean Section in Patient with Uncontrolled Hyperthyroidism and Severe Mitral Regurgitation - Khaidar, Reyfal; Subiantoro, Andri; Sugiharto, Wahyu; Prasiska, Tomy Oky (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2023)
Background :The prevalence of hyperthyroidism in pregnancy approximately 0.05% to 3% and mostly caused by Graves’ Disease (GD). The prevalence of Hyperthyroid Heart Disease (HHD) in pregnancy is 3.87%. Uncontrolled hyperthyroidism during pregnancy can increase maternal and fetal mortality. We report a case of a pregnant woman with uncontrolled hyperthyroidism and severe mitral regurgitation that underwent cesarean section with spinal anesthesia for delivery.Case Illustration :A 33 years-old patient G4P1A2 visited the Obstetric-Gynecology outpatient clinic at our hospital at 23 weeks of gestation (WoG) due to uncontrolled hyperthyroidism caused by GD that diagnosed 3 years ago and shortness of breath. The echocardiography test obtained severe mitral regurgitation and left atrial dilatation with 58% LVEF. It was decided to maintain the pregnancy till the fetus is viable while still monitoring the patient’s condition. At 32 WoG, the patient came to the ED due to shortness of breath, chest pain, and nausea. Fetal movement and fetal heart rate (FHR) were within normal limits. The patient was given a nasal cannula at 3 liters/minute, extra furosemide 20 mg, and fetal lung maturation with dexamethasone injection. The patient was prepared for termination by cesarean section. Spinal anesthesia was performed in a sitting position using a 27 G spinal needle. Inserted at L 3-4, using a low dose of heavy bupivacaine 0.5% 7.5 mg combined with 25 g fentanyl and 0.1 mg morphine intrathecally. C-section was successfully performed and hemodynamics during surgery was stable, resulting the delivery of a preterm baby who weighed 1.9 kg at birth and the baby was transferred to the NICU for further treatment.Conclusion : Spinal anesthesia with low dose bupivacaine combined with opioids for cesarean section was revealed maternal and neonate safe.